2014
DOI: 10.1037/neu0000066
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements reveal impaired inhibitory control in adult male fragile X premutation carriers asymptomatic for FXTAS.

Abstract: Objective: Fragile X premutation carriers (fXPCs) have an expansion of 55 —200 CGG repeats in the FMR1 gene. Male fXPCs are at risk for developing a neurodegenerative motor disorder (FXTAS) often accompanied by inhibitory control impairments, even in fXPCs without motor symptoms. Inhibitory control impairments might precede, and thus indicate elevated risk for motor impairment associated with FXTAS. We tested whether inhibitory impairments are observable in fXPCs by assessing oculomotor performance. Method: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 89 publications
4
16
1
Order By: Relevance
“…Regarding parents first concerns our results indicated that parents express their concern at all ages of their childrens and are much more significant between 44 and 33 months of age; however, other work 26,27,28 , show that parents generally begin to suspect developmental problems in their children between 12 and 24 months of age. There is a significant association between the age of the child's parents at birth and the subsequent risk of developing an Autism Spectrum Disorder (ASD), Our results are consistent with 29,30,31 who showed that the increase in ASD was not only limited to advanced parental age, but also to the age difference between them. These same results detected a significant influence of parental age on the risk of autism.…”
supporting
confidence: 88%
“…Regarding parents first concerns our results indicated that parents express their concern at all ages of their childrens and are much more significant between 44 and 33 months of age; however, other work 26,27,28 , show that parents generally begin to suspect developmental problems in their children between 12 and 24 months of age. There is a significant association between the age of the child's parents at birth and the subsequent risk of developing an Autism Spectrum Disorder (ASD), Our results are consistent with 29,30,31 who showed that the increase in ASD was not only limited to advanced parental age, but also to the age difference between them. These same results detected a significant influence of parental age on the risk of autism.…”
supporting
confidence: 88%
“…Moreover, greater activation in the left cerebellar VII was associated with fewer errors for PM females; while for controls, greater cerebellar activity correlated with quicker antisaccade responses. Structural cerebellar and prosaccade/antisaccade performance associations have previously been revealed for controls, in which cerebellar lobules I–V and IX–X volumes were found to correlate with antisaccade speed; and PM males, in which cerebellar lobule VI–VII volume was found to correlate with the difference in antisaccade‐prosaccade latency [Wong et al, ]. Together, these studies both highlight the pivotal role that cerebellar lobules V–VII play in the control of saccades.…”
Section: Discussionmentioning
confidence: 68%
“…This is completed through internal feedback mechanisms (via projections to and from brainstem within the middle and superior cerebellar peduncles) allowing for adaptation and motor learning [Schubert and Zee, 2010;Scudder et al, 1996;Zee and Walker, 2009]. However differences in the associations are likely due to i) the interleaved presentation of prosaccade and antisaccade trials and functional neural activation of the cerebellum in the current study, rather than block presentation of similar trials and volumetric measures as presented by Wong et al [2014]. Thus, we propose that the current and previous associations between the cerebellar lobules and executive function indicate differential cerebellar learning outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…Eye movements have been used to assess inhibitory control, a component of executive function, in PM carriers asymptomatic for FXTAS (55). Impairments were detected in the oculomotor domain of these individuals; specifically, PM carriers show increased reaction times in the anti-saccade task and increased inhibitory cost from early life, as compared to healthy controls.…”
Section: Modeling Human Pm and Fxtas In Micementioning
confidence: 99%